ANALISIS KEMAMPUAN BERPIKIR KREATIF DALAM PENYELESAIAN SOAL MATEMATIKA - Ayundia, Ulia Devi Anti; Sutini, Sutini; Prasetyo, Agung (MES: Journal of Mathematics Education and Science, 2025)
This study aims to analyse the mathematical creative thinking abilities of junior high school students on the subject of curved-sided shapes: spheres. Creative thinking abilities were analysed based on four indicators, namely fluency, flexibility, originality, and elaboration. This study used a qualitative descriptive method with ninth-grade students at Sidoarjo State Junior High School as the subjects. The instrument used was an essay test consisting of four questions designed to explore students' creative thinking abilities. The results showed that the percentage of achievement for the fluency indicator was 80%, flexibility 70%, originality 70%, and elaboration 55%. These findings indicate that students have begun to develop good creative thinking skills, but there is still room for improvement, especially in the areas of flexibility and elaboration. These results can serve as a basis for teachers in designing learning activities that encourage the optimal development of students' creativity.